2001
DOI: 10.1242/jcs.114.10.1875
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear dispositions of subtelomeric and pericentromeric chromosomal domains during meiosis in asynaptic mutants of rye (Secale cereale L.)

Abstract: The nuclear dispositions of subtelomeric and pericentromeric domains in pollen mother cells (PMCs) were tracked during meiosis in wildtype and two asynaptic mutants of rye (Secale cereale L.) by means of fluorescence in situ hybridization (FISH). Homozygotes for sy1 and sy9 non-allelic mutations form axial elements during leptotene of male meiosis, but fail to form synaptonemal complexes. Consequently, recombination is severely impaired, and high univalency is observed at metaphase I. Simultaneous FISH with pS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…We showed that, in early leptotene, chromosome arms were condensed and organised into irregular globular subdomains with telomeres and centromeres pointing to opposite poles of the nucleus. This condensed early chromosome conformation and the bipolar orientation of telomeres versus centromeres was in agreement with several previous studies analysing chromatin dynamics in wheat-rye introgression lines Maestra et al, 2002;Mart ınez-P erez et al, 1999;Mikhailova et al, 2001;Schwarzacher, 1997). We demonstrated that this condensed chromatin structure coincided with recombination initiation by numerous nucleus wide DSBs, whereas homologous chromosome arms were located at considerable distances from one another (Figure 7).…”
Section: Chromatin Reorganisation Precedes Chromosome Juxtaposition A...supporting
confidence: 93%
“…We showed that, in early leptotene, chromosome arms were condensed and organised into irregular globular subdomains with telomeres and centromeres pointing to opposite poles of the nucleus. This condensed early chromosome conformation and the bipolar orientation of telomeres versus centromeres was in agreement with several previous studies analysing chromatin dynamics in wheat-rye introgression lines Maestra et al, 2002;Mart ınez-P erez et al, 1999;Mikhailova et al, 2001;Schwarzacher, 1997). We demonstrated that this condensed chromatin structure coincided with recombination initiation by numerous nucleus wide DSBs, whereas homologous chromosome arms were located at considerable distances from one another (Figure 7).…”
Section: Chromatin Reorganisation Precedes Chromosome Juxtaposition A...supporting
confidence: 93%
“…We used such criteria as the number and position of nucleoli in meiocyte nuclei [43,44], character of ASY1 localization, distribution and share of centromeres [17][18][19], and the cell shape [21] described for wheat, barley and rye. In the course of meiocyte development, the nucleoli fuse (reunite) into one before or during leptotene [43,44]; as a result, during the leptotene-to-zygotene transition, one large nucleolus localizes on the nucleus periphery [7,8,21,22,44,45]. For both wheat and rye, full telomere aggregation coincides with nucleoli fusion [19,21,24,25,44].…”
Section: Defining the Time-course Of Early Prophase Progress In Wheat...mentioning
confidence: 99%
“…To date, no plants without the bouquet structure were found in the studies [3,6,13,14]. The telomere dynamics at the early meiotic prophase is well known in such agricultural crops as maize (Zea maize) [8,15,16], barley (Hordeum vulgare) [17][18][19], rye (Secale cereale) [20][21][22][23] and wheat (Triticum aestivum) [7,19,24,25]. In barley, the telomeric bouquet clustering is completed in late G2; by leptotene, the telomeres are clustered [18], or the bouquet forms during leptotene, persisting during zygotene [17,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During early meiotic PI, telomeres aggregate on the nuclear envelope, forming a cluster or bouquet [102][103][104], facilitating homologous chromosome sorting. The timing of telomere bouquet formation differs across species, appearing earlier at PI in wheat and rye and later in maize [24,105,106]. After the formation of the telomere bouquet, SC formation is initiated near the telomeres during early PI, progressing lengthwise pairing as PI proceeds (Figure 1) [107][108][109].…”
Section: Meiosis In Allopolyploidsmentioning
confidence: 99%